Cognitive Ethnography of Cultural Artifacts of Adu Mancung Weaving Motifs of the Suku Baduy Luar in Lebak, Banten - I Mahendra; W S Abioso (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to examine how the Baduy Luar tribe creates Adu Mancung weaving and the values inherent in Adu Mancung weaving. This study employs a qualitative approach with a descriptive analysis to conduct a cognitive ethnographic study of the Baduy Luar tribe's Adu Mancung weaving motif. The research began with a review of existing literature on the Baduy Tribe. Observations were made in 2021 in Kanekes Village, Lebak, the home of the Baduy Luar people, and in-depth interviews were conducted with Jaro (local leader), guides, and Baduy Luar weavers. The results of this research is the Adu Mancung weaving motif holds sacred value for the Outer Baduy Tribe. This weaving is used in traditional wedding proposals, Tanam Padi, Kawalu and Seba ceremonies. This weaving is presented to the man during the "Nanyaan" event as an offering by the prospective bride. This weaving motif is made up of two contradictory triangles, so it is called Adu Mancung. The motif represents the couple's commitment to the Baduy Luar tribe's monogamous culture. The Baduy Luar tribe's woven fabrics are created by weavers using the "pakara tinun," a traditional weaving tool. From an early age, Baduy children are taught to weave as a culture passed down from generation to generation. This research is expected to serve as a reference for the Baduy Luar tribe's weaving and aid in preserving the Baduy Tribe's culture in the academic paper